Ammonium Toxicity Alleviation by Silicon is Dependent on Cytokinins in Tomato cv. Micro-Tom - Barreto, Rafael Ferreira [UNESP] (2021)
The objectives were to verify the effects of the lack of cytokinins (CKs), comparing tomato cv. Micro-Tom (MT, wild type) to MT CKX2 (transgenic with less CKs) fed with nitrate (NO3−) and ammonium (NH4+), in the presence and absence of silicon (Si); verify if the attenuation of NH4+ toxicity by Si depends on the increase of CKs in MT; and verify if 6-benzyladenine (6-BA) attenuates NH4+ toxicity in MT. Three experiments were performed with treatments via nutrient solution. First, MT and MT CKX2 were grown with NO3− or NH4+ (5.9 mmol L− 1), in the absence and presence of Si (1.28 mmol L− 1). Second, MT was grown with NO3− or NH4+ (5.9 mmol L− 1), in the absence and presence of Si (1.28 mmol L− 1). Third, MT was grown with NO3− or NH4+ (5.9 mmol L− 1) and 6-BA (from 1e−10 to 1e−6 mol L−1) associated with NH4+. The MT and MT CKX2 had a decrease of 18% and 48% in the shoot dry weight, respectively, when fed with NH4+, compared to NO3−. Si attenuated NH4+ toxicity in MT, but not in MT CKX2. This attenuation in MT was accompanied by a decrease in trans-zeatin (tZ) content in the roots and increase in the shoots. 6-BA did not improve the shoot growth of MT fed with NH4+. In conclusion, the alleviation of NH4+ toxicity by Si was dependent on the increase in tZ content in shoots. In CK-deficient plants, Si did not alleviate NH4+ toxicity, and 6-BA did not alleviate NH4+ toxicity in MT shoots.